Interaction behavior between chitosan and pepsin - Boeris, Valeria (2011)
The interaction between chitosan (a positively charged polysaccharide) and the acidic protein pepsin was studied by the use of dynamic light scattering, electronic spectroscopic approaches and measurements of thermodynamic functions. An interaction, mainly electrostatic, between the enzyme and the cationic polymer was found. The size of the soluble complexes formed between pepsin and chitosan  was shown to depend on the pH value. Chitosan was seen to interact with the surface of the pepsin molecule, but no modification was observed in the pepsin secondary structure or in its chemical and thermal thermodynamic stability.